New wine in a very old bottle: Canadian Protestant missionaries as facilitators of development in central Angola, 1886-1961. - Byam, Paul C. (University of Ottawa (Canada), 1997)
This dissertation assesses the role played by Canadian Protestant missionaries in promoting development in Central Angola from 1886 to 1961. It is a case study of the Congregational and United Church of Canada missionaries who worked principally among the Ovimbundu during the heyday of Portuguese colonialism in Africa. The study focuses briefly on the cultural background of the missionaries and the social and scientific advance in the Western world that enabled them to become facilitators of development overseas. This background is contrasted with the more lethargic pace of development in mainland Portugal and its overseas territories. Though distrusted by the Portuguese and African authorities alike at the beginning of their enterprise, the Protestant missionaries were soon welcomed more readily into African villages once it became clear that they could provide African communities with a constructive alternative to the depredations of Portuguese colonialism. By focusing primarily on extractive industries and on plantation economies, the Portuguese State had done very little to promote wholesome development in Angola. Many villagers were forcibly taken from their communities to meet the labour demands of plantations, big companies and public construction projects. The authorities gave little thought to the disruptions that such an exodus caused within individual communities or within the urban districts that did not yet have the facilities to cope with the heavy influx of labourers. To further compound the situation, Portuguese officials tampered with the traditional political structure of African villages, often replacing recognized leaders with their own appointees. Ultimately, they did nothing to preserve the social fabric of Angola and sought, half-heartedly, to replace it with Portuguese traditions. The Protestant missionaries, while seeking primarily to gain Christian converts in Africa, deliberately exposed the Angolans in their mission field to the skills and tools that would enable them to improve their lot under Portuguese domination. Church organization partially replaced the sociopolitical structures that had been weakened or destroyed by Portuguese colonialism. Western education, medical expertise and the application of various agricultural techniques gave the Protestants an advantage that even their Catholic counterparts, ambiguously aligned with the State, did not enjoy. Without seeking to overthrow Portuguese colonialism in Angola, the Protestant missionaries inevitably aided in its downfall by making the Angolans more self-sufficient and keenly aware of their rightful place in the global community.
Keywords: History, Church.